Formação de professores no Brasil: um estudo a partir da Revista Brasileira de Estudos Pedagógicos - RBEP (1990/2000) - Morais, Isabela Cristina Santos de (2021)
This study deals with the development of ideas about teacher education in Brazil from 1990 to 2000, having as its main source of research, the articles of the Brazilian Journal of Pedagogical Studies (RBEP), a journal created in 1944 by INEP. Our study understood the years 1990/2000 as a time frame, considering, for its establishment, important facts for teacher education, such as the promulgation of LBB 9,394/96, and events related to the research source, such as the consolidation of proximity to the academic Community. In our hypothesis, we understand the Journal as a formative space based on the definition of the space for writing in the journal for the dissemination of pedagogical theories and socialization of research, acting as an element for dialogue and development of the desired profile for teacher education. Therefore, we investigated the development of these ideas from the journal's publications, realizing how this theme was being problematized in the articles published considering the time frame of the years 1990-2000. Our theoreticalmethodological contribution was based on the perspective of the History of Education, comprising as concepts the training of Teachers Saviani (2012), Gatti (2010), Stamatto (2019), Tardif and Lessard (2012) and the Pedagogical Press in understanding of Nóvoa (1992) and Catani (1996); the circulation of ideas from Chartier (2002) and content analysis by Bardin (2016) and Moraes (1999). With this study, we seek to contribute to the understanding of the development of Teacher Education in the 1990s, collaborating with the research center in the area of fundamentals of education.